Negative surface streamers propagating on TiO2 and γ-Al2O3-supported Ag catalysts: ICCD imaging and modeling study. (25th May 2018) - Kim, Hyun-Ha; Teramoto, Yoshiyuki; Ogata, Atsushi; Kang, Woo Seok; Hur, Min; Song, Young-Hoon
Abstract: Surface streamers propagating on the surface of titanium dioxide (TiO2 ) and alumina ( γ -Al2 O3 ) were studied in negative polarity using intensified charge coupled device (ICCD) imaging and numerical simulation. Detailed time-resolved ICCD images of cathode-directed streamers (CDSs) emanating from a ground electrode are first presented in this report. Instead of primary streamers in positive polarity, only a glow-like discharge appeared in the early stage at the cathode under negative polarity. After this discharge disappeared, a counter-propagating CDS initiated from the ground electrode (anode). Numerical simulation indicated that strong electric fields at the pellet-anode and the formation of positive ion rich local spots were the main reason for the CDS formation near the ground electrode. The maximum velocity was 750 km s −1 for Ag-supported γ -Al2 O3 and 550 km s −1 for Ag-supported TiO2, respectively. In contrast to the CDS in the gas-phase with a positive polarity, the CDS in a catalyst packed-bed under negative polarity showed more branching and a larger number of streamers in the presence of oxygen than in pure N2 .